Competition in Higher Education Branding and Marketing National and Global Perspectives (Springer International Publishing, 2018)
This volume provides a critical examination of branding and marketing in higher education from national, regional, and global perspectives. Contributors with expertise in higher education, sociology, comparative and international education, marketing, rankings, and educational philanthropy use novel theoretical frameworks and cases from Africa, Asia, Europe, Latin America, and the US to map the brandscape of higher education. Empirical cases and literature analysis show that brand building is becoming a deliberate goal for higher education. This book illustrates student-institution dynamics, as well as the critical role of policy and professionalization to support branding and marketing strategies in higher education in relation to equity. .